(untitled) (Editora Impacto Científico, 2025)
This article aims to present the impacts caused by the period of social isolation, due to the COVID-19 pandemic, on the school routine of students with Autism Spectrum Disorder (ASD). The methodology used in this work was quantitative in nature, with a bibliographic review and the application of a questionnaire, prepared with dissertative and objective questions, answered by teachers from a State School in the Municipality of Teodoro Sampaio, SP. Students with ASD often need support to carry out their school activities, so the main objective was to understand how remote care was provided, what the main barriers were and the impacts caused. The results showed that the COVID-19 pandemic has brought many challenges to teaching, with the inclusion of remote teaching in which teachers have had to reinvent their teaching methodologies. We conclude that remote teaching is challenging and that teacher intervention is essential and indispensable in the teaching process.